2011
DOI: 10.1128/jb.01281-10
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome of the Plant Growth-Promoting RhizobacteriumPseudomonas putidaBIRD-1

Abstract: We report the complete sequence of the 5.7-Mbp genome of Pseudomonas putida BIRD-1, a metabolically versatile plant growth-promoting rhizobacterium that is highly tolerant to desiccation and capable of solubilizing inorganic phosphate and iron and of synthesizing phytohormones that stimulate seed germination and plant growth.Bacteria that efficiently colonize the rhizosphere and stimulate plant growth through direct or indirect mechanisms are referred to as plant growth-promoting rhizobacteria (PGPR). Plant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 4 publications
1
36
0
1
Order By: Relevance
“…Recently, it has been suggested that many of the resident GIs in a single prokaryotic genome originated from the same source, considering their similar genomic signature compositions (56). The identity of the donor microorganism(s) of the 12 GIs selected in this work is unknown, because the results from sequence alignments did not show homology with any sequence longer than 4 kb in the databases, including P. putida strains BIRD-1, S16, and B6-2 (41,64,72).…”
Section: Discussionmentioning
confidence: 92%
“…Recently, it has been suggested that many of the resident GIs in a single prokaryotic genome originated from the same source, considering their similar genomic signature compositions (56). The identity of the donor microorganism(s) of the 12 GIs selected in this work is unknown, because the results from sequence alignments did not show homology with any sequence longer than 4 kb in the databases, including P. putida strains BIRD-1, S16, and B6-2 (41,64,72).…”
Section: Discussionmentioning
confidence: 92%
“…Recently, a few P. putida strains have been isolated from hospital environments (von Graevenitz and Weinstein, 1971; Galli et al, 1992; Yoshino et al, 2011; Molina et al, 2013, 2014, 2016). The ubiquitous character of this microorganism has been linked to its broad metabolic potential, its ability to produce a large variety of secondary metabolites that may enable colonization of different environments and a complex array of sigma factors and two-component regulatory systems that allow a fast adaptation to environmental changes (Matilla et al, 2011; Udaondo et al, 2012, 2013, 2016; Planchamp et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Genome annotation of several natural chloramphenicol-resistant P. putida strains failed to show any specific chloramphenicol-modifying enzymes (36,41,45,67); however, Godoy and colleagues (23) showed that P. putida mutants in the multidrug TtgABC pump exhibited compromised growth in the presence of chloramphenicol (21). Further studies in P. putida DOT-T1E confirmed the role of the TtgABC efflux pump in tolerance to chloramphenicol and other toxic compounds while unveiling the molecular mechanisms involved in the regulation of the expression of this pump in this strain (14,18,58).…”
mentioning
confidence: 99%